State of the art and development of gold dental alloys - Rudolf, Rebeka; Majerič, Peter; Vastag , Djendji; Lazić, Vojkan (Anali PAZU, 2024)
The article discusses the history, development, and properties of gold dental alloys. Alloys produced by Zlatarna Celje d.o.o. are certified medical devices in class IIa according to Regulation (EU) 2017/745, indicating a moderate level of risk. Alloys for porcelain crowns and bridges have a special status, requiring specific chemical composition and processing. Future development should aim to minimize biological risks and corrosion, achievable with highly noble alloys with stable microstructure. Dental alloys must not be ferromagnetic. Correct chemical composition is crucial for each patient, as the market offers various alloys suitable for individuals with different allergies and specific conditions in their oral cavity. It is important to follow the manufacturer's recommendations to ensure the quality fabrication and installation of dental prosthetic constructions.
Keywords: state of the art; development; gold dental alloys; properties; use